Food and Feeding of Vultures in Rajasthan, India - Chhangani, Anil Kumar (Indian Forester, 2010)
During the study period from July, 2004 to July, 2008, a total of 5735 vultures of seven different species were recorded in different geographical regions of Rajasthan. This includes long-billed vulture (Gyps indicus), white-backed vulture (Gyps bengalensis), red-headed vulture (Sarcogyps calvus) and Egyptian vulture (Neophron percnopterus) as residents and Himalayan griffon (Gyps hymalayansis), Eurasian griffon (Gyps fulvus) and Cinerarious vulture (Aegypius monachus) as winter migrants. Their presence near the carcass dumping grounds in villages, towns and cities is common. Cow carcasses were the main source of food (74%) followed by buffalos (12%), wild animal (8%) carcass (including chinkara, bluebull, black buck, chital and rabbits) and the remaining 6% are other livestock (which includes camel, goat, sheep, donkey, horses, dogs and pigs) at different feeding sites (n=138).